Gold-catalyzed stereoselective cycloisomerization of allenoic acids for two types of common natural γ-butyrolactones - Jing Zhou (Nature Portfolio, 2018)
Gamma-butyrolactones are widespread in Nature, however direct catalytic methods to access them are limited. Here, the authors report a gold-catalyzed cycloisomerization of allenoic acids to acces γ-butyrolactones and apply it to the asymmetric synthesis of xestospongienes E, F, G, and H and other naturally occurring lactones.